Asynchronous Stochastic Approximations - Borkar, Vivek S. (SIAM journal on control and optimization, 1998)
The asymptotic behavior of a distributed, asynchronous stochastic approximation scheme is analyzed in terms of a limiting nonautonomous differential equation. The relation between the latter and the relative values of suitably rescaled relative frequencies of updates of different components is underscored.